Allee effects: empirical analyses of wild British butterfly populations and theoretical implications for population synchrony - Dooley, C (2014)
An Allee effect is a density-dependent process that can be responsible for the extinction of small populations. This thesis focuses on the detection of Allee effects, along with other density-dependent processes, and their influence on population synchrony. In chapter 2 I investigate the spatial variation in influential density-dependent processes and density-independent weather factors for the large skipper butterfly Ochlodes sylvanus across its British range. I find both qualitative and quantitative spatial variation in these processes and factors driving population dynamics. In chapter 3, I develop and test a Bayesian methodology, that I then use in chapter 4 to analyse local population level dynamics for 38 British butterfly species. For 35 of these species I found population level Allee effects and also found that phylogeny significant influenced a species’ susceptibility to Allee effects. Finally, in chapter 5 I examine the influence Allee effects have on network population synchrony in a theoretical framework.